2019
DOI: 10.30782/jrvm.567561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Slaughter Age and Season on Final Weight and Carcass Characteristics in Holstein-Friesian Cull Cows

Abstract: The objective of this study was to quantify the effects of the factors including age at slaughter and slaughter season on certain carcass characteristics in cull cows. Data from 159 Holstein-Friesian cull cows were used and the cows were divided into three age groups including, very young (<2 years), young (2-3years) and mature (>3years). Statistical analysis was carried out by the least-squares method as applied in a general linear model (GLM). Results indicated that mature cull cows were characterised by hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In this regard, calves come to the forefront. During the fattening period, although calves reach almost twice their initial fattening weight, the increase in 1‐year‐olds is 70%, and in 2‐year‐olds, it decreases up to 40%–50% (Ardıclı, 2019 ). The present study showed that hair goat weight gain is important in the first year after birth by comparing the mean values of carcasses of both young and adult goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, calves come to the forefront. During the fattening period, although calves reach almost twice their initial fattening weight, the increase in 1‐year‐olds is 70%, and in 2‐year‐olds, it decreases up to 40%–50% (Ardıclı, 2019 ). The present study showed that hair goat weight gain is important in the first year after birth by comparing the mean values of carcasses of both young and adult goats.…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive relationship between age and carcass bone ratio. In other words, increase in the age causes an increase in the bone composition of carcass (Ardıclı, 2019 ). In line with the current study's results, it has been identified that ageing leads to an increase in the carcass's bone ratio, consistent with Ardıclı’s research.…”
Section: Discussionmentioning
confidence: 99%